IMPLEMENTATION OF THE PRINCIPLES OF INCLUSIVE EARLY CHILDHOOD LEARNING AND MANAGEMENT IN INDONESIA - Marnita Bancin; Nurul Zahriani Jf; Hani Putri (Proceeding International Seminar of Islamic Studies, 2023)
This paper aims to find out the principles of inclusive early childhood education as well as strategies to develop management planning for inclusive early childhood education so that children get maximum educational opportunities, and make it easier for institutions to implement inclusive early childhood principles according to children's needs. The method used is a qualitative research method with a library research approach (library study) with techniques and data analysis obtained from books, journals, articles, theses and other sources. The results of this study indicate that the principles and management of inclusive PAUD education must be considered properly in accordance with the strategies implemented, starting from identifying children's needs, children's potential, and obstacles that occur in children according to the principles and management of inclusive PAUD. This is very well taken care of so that its management runs according to the standard goals to be achieved by the Institution, seeing the many conditions of children with special needs by the government in Inclusive PAUD. Management or management of inclusive education in PAUD cannot be separated or cannot be separated from education management in general.